ANALISIS CAMPUR KODE BAHASA ARAB DALAM GRUP WHATSAPP LEMBAGA DAKWAH KAMPUS UNIVERSITAS AL AZHAR INDONESIA - Mujahidah Fharieza Rufaidah; Nurazizah Salshabila; Nur Hizbullah (Prasasti: Journal of Linguistics, 2021)
The use of code-mixing in oral and written forms is one of the factors that produced a language variety neither in direct communication or undirected communication through social media. One of the cases is the WhatsApp application. This study discusses the phenomenon of Arabic code-mixing that used in the WhatsApp Group of Da'wah institute in Al Azhar University of Indonesia. The purpose of this study was to identify the Arabic code-mixing forms in the LDK KARISMA Al-Azhar University of Indonesia WhatsApp group and to obtain the motivation of the code-mixing usages in direct-communication or the communication that through the social media. Code-mixing and its form were analyzed using sociolinguistic theory, then to examine the context of WhatsApp conversation that contains code-mixing, the researcher used discourse analysis theory. Researchers found 33 mixed codes in 3 forms, which is the form of words, phrases, and clauses. To discover the motivation of using Arabic code-mixing, the researcher made an online questionnaire and described it through descriptive statistical techniques with a total of 27 respondents. The results of the online questionnaire found that the majority of the motivation of the members of LDK KARISMA UAI used Arabic code-mixing in a communication aimed as a means of supporting da'wah activities.